Evaluation of the Realization of Expenditure on Cigarette Tax Revenue Sharing in the City of Manado - Grasela Abigail; Harijanto Sabijono; Steven Tangkuman (PT FORMOSA CENDEKIA GLOBAL, 2023)
Realization of the Budget is very important in the implementation of Expenditures. Cigarette tax DBH revenue is a source of local own-source revenue (PAD) because it is a very potential source of local revenue and can be collected efficiently, effectively and economically, so that it can play a bigger role in efforts to increase regionally-sourced income (PAD). This study aims to evaluating the appropriateness of the realization of spending on cigarette tax revenue-sharing and knowing the records. The object of this research is the Regional Financial and Asset Board of Manado City. This type of research is descriptive qualitative using interview techniques, observation, data collection as well as documentation. The results of this study are the Realization of Cigarette Tax Revenue Sharing Fund Expenditure in 2018-2021, that the realization of cigarette tax revenue sharing expenditure has decreased in 2020 and 2021, then in 2018 and 2019 it has increased. The lowest realization was in 2020 and 2021 where the realization was quite low, namely only reaching 94.35%, for recording it was in accordance with existing regulations, namely PP 71 of 2010.